Evaluation of urban public ground anthropogenic modification in the municipality of São Carlos-SP - de Oliveira, Vinícius Gustavo [UNESP]; Corrêa, Rony Felipe Marcelino; de Oliveira, Suzana Aparecida Ferreira; Asciutti, Gustavo Augusto Mendonça; Jacó, Ana Paula; Mazzuco, Giulia Guillen; Menezes, Denise Balestrero (Revista Brasileira de Geomorfologia, 2021)
Alteration in the natural conditions of a land, due to intensive human action, generates several types of impacts to the environment. In general, these impacts may lead to the formation of anthropogenic deposits, features or vectors, which may lead to unpredictable soil conditions, changes in the hydrogeological regime and infiltration of pollutants into the ground water. This work aims to characterize the different types of deposits, features and anthropogenic vectors, and to delimit the area of occurrence of these deposits, in a social interest area, in Vila Monte Carlo neighborhood, city of São Carlos-SP Brazil. We found Erosions, formation of anthropogenic river spring, sterile waste pile, mineral waste, rainwater gallery, urban occupation areas and wastes of civil construction. In addition, natural features were found, such as natural soils (soil residual from Botucatu), and area with a high slope which outcrop silicified sandstones of the Botucatu Formation. In general, the area presents several problems that make it difficult to use this area for urban occupation. Thus, we carried out a mapping, identifying the types of anthropogenic changes, and the interrelationships of vectors, features and deposits, using field surveys and geoprocessing tools, generating a recognition analysis and the definition of constraints for that area.
Avaliação da transformação antropogênica de terreno público urbano no município de São Carlos-SP
Keywords: Anthropogenic Deposits; Technogenic Deposits; Urban Geology; Urban Planning